Developing Mathematical Knowledge Through Social Justice Pedagogy with Young Adult Arab Women - Tanko, M.G.; Atweh, Bill (Mathematics Education Research Group of Australasia Inc, 2012)
The study involved a group of Middle Eastern Muslim women learning mathematics through social justice pedagogy. The findings suggest that the involvement of students in social justice issues has not lead into a decline in their opportunity to learn mathematical content as set in the course. However, this approach has helped them to develop significant mathematical knowledge beyond the basic numeracy skills expected of them. In addition, this study demonstrated how a focus on mathematical content can be maintained while students are involved in social issues in mathematics learning.